Can splitting influence corporate strategy? Exploring the effects of TMT faultlines on internationalization speed. - Jia Lv; Jie Zhou; Yajun Liu (PLoS ONE)
On the basis of upper echelons theory, this paper examines the effect of TMT faultlines on internationalization speed and considers the contextual factors that may affect the focal relationship. We focus on A-share listed manufacturing enterprises in the Shanghai and Shenzhen stock markets from 2010 to 2016 to explore the nexuses. The conclusions indicate that TMT faultlines exerts a significant negative influence on the speed of internationalization. However, the presence of executives shareholding and dynamic capabilities serve to mitigate the negative impact to some extent. These findings hold both theoretical and practical significance for Chinese firms' internationalization in the context of the 'double-loop strategy'.